COVID-19 in Indonesia Impacts on the Economy and Ways to Recovery - Ing, Lili Yan; Basri, M. Chatib (Routledge-ERIA Studies in Development Economics, 2022)
This book assesses the impacts of COVID-19 on the Indonesian economy, particularly on employment, education, poverty, trade, and macro economy. The book explains how fiscal and monetary stimulus work and the roles of local governments in managing stimulus. It also presents ways to recovery and lessons learnt from countries that have found success in mitigating the economic impacts of the pandemic (China, Germany, Singapore, and Vietnam). This book will be a useful reference for policy makers, scholars, students, and public audience working or having interest in the fields of development economics, trade, health economics, economics, and East Asia.